Integration of Islamic Education Curriculum to Enhance the Social Character of Vocational High School Students - Hatta Fakhrurrozi; Masturah Minabari; Fatimah Saguni; Sitti Nadirah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
Adolescence's middle years are fraught with problems that force them to make good or bad decisions in their social interactions. Schools play an important role in guiding students' development in the right direction. The purpose of this research is to investigate a model for integrating the Tarbiyah Islamiyah curriculum in order to improve the character of students. The vocational high school Bina Potensi Palu is the site of this research. This study is a qualitative-descriptive. The respondents included the principal and four teachers who were directly involved in tarbiyah islamiyah activities. Data was gathered through an in-depth interview technique and presented following the reduction and triangulation processes. The findings of this study revealed that: 1) the tarbiyah Islamiyah integration process took two forms, that is integration into Islamic religious education subjects and integration into extracurricular activities that were held every weekend. Integration using Fogarty's shared model; 2) Tarbiyah islamiyah in schools implements a limited boarding school system; the authors refer to it as